β-carotene Rescues Busulfan Disrupted Spermatogenesis Through Elevation in Testicular Antioxidant Capability - Dongxue Ma; Pengfei Han; Mingji Song; Hongfu Zhang; Wei Shen; Guian Huang; Minghui Zhao; Qingyuan Sun; Yong Zhao; Yong Zhao; Lingjiang Min (Frontiers Media S.A., 2021)
β-carotene, precursor of vitamin A, is an excellent antioxidant with many beneficial properties. It is a lipid-soluble antioxidant and a very effective quencher of reactive oxygen species (ROS) to reduce the oxidative stress. In contrast to vitamin A, β-carotene is not toxic even consumed in higher amount when it is delivered from natural plant products. Recently, we found that β-carotene acts as a potential antioxidant in the oocyte to improve its quality. Even though many studies have been reported that β-carotene has the beneficial contribution to the ovarian development and steroidogenesis, it is unknown the effects of β-carotene on the spermatogenesis. This investigation aimed to explore the hypothesis that β-carotene could improve spermatogenesis and the underlying mechanism. And we found that β-carotene rescued busulfan disrupted spermatogenesis in mouse with the increase in the sperm concentration and motility. β-carotene improved the expression of genes/proteins important for spermatogenesis, such as VASA, DAZL, SYCP3, PGK2. Moreover, β-carotene elevated the testicular antioxidant capability by the elevation of the antioxidant glutathione and antioxidant enzymes SOD, GPX1, catalase levels. In conclusion, β-carotene may be applied for the infertile couples by the improvement of spermatogenesis, since, worldly many couples are infertile due to the idiopathic failed gametogenesis (spermatogenesis).